Exploring Elementary Science Teaching and Learning in Canada - Tippett, Christine D.; Milford, Todd M. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This edited volume showcases current science education research in Canada, from pre-Kindergarten to Grade 7, conducted in Canada by a diverse group of researchers from across the country. We draw on the themes that emerged from our previous book, Science Education in Canada: Consistencies, Commonalities, and Distinctions, to guide the structure of this book on elementary science education research. In particular, chapters on science teacher preparation; Indigenous perspectives; environmental education; science, technology, engineering, and mathematics (STEM); and science, technology, society, and the environment (STSE) reflect a Canadian perspective. However, these themes are of global interest and authors include ideas for how science education research in Canada might be used by academics and researchers in other countries. This book builds a cohesive picture of current elementary science education research in Canada, highlighting themes that will resonate with international readers. .
1, Providing a Space for Canadian Science Education Research -- 2, Changes in Discourse Patterns during Scientific Inquiry: A Co-teaching Model -- 3, Adopting Universal Design for Learning as a Means to Foster Inclusive Science Teaching and Learning -- 4, Science in the Spotlight: What Are Monsters Made Of? (A Performative Inquiry) -- 5, Teaching the Engineering Design Process: Pre-service Teachers' Professional Development in a Community of Practice -- 6, Is this a course about science? Tensions and Challenges with Engaging Preservice Elementary and Middle Years Teachers in Science Learning -- 7, Professional Learning Using a Blended-Learning Approach with Elementary Teachers Who Teach Science: An Exploration of Processes and Outcomes -- 8, Extending Scientific Literacy through Indigenous Hawaiian Epistemology -- 9, Using Bee-Bots in Early Learning STEM: An Analysis of Resources -- 10, Connecting Children to Nature through Scientific Inquiry: The Impact on Children's Well-being -- 11, Using Wearable GPS Technology to Explore Children's Authentic Interest in Nature -- 12, Nature is our Classroom: Place-conscious Pedagogy and Elementary Science Education. .
Keywords: Science -- Study and teaching; Education -- Curricula; Teachers -- Training of; Education and state; Science Education; Curriculum Studies; Teaching and Teacher Education; Educational Policy and Politics